Effect of high‐fat diet and growth stage on the diversity and composition of intestinal microbiota in healthy bovine livestock. (7th June 2017) - Jiao, Shengyin; Cao, Hui; Dai, Yue; Wu, Junhui; Lv, Jia; Du, Renjia; Han, Bei
Abstract: BACKGROUND: This study aimed to investigate the composition of bacteria in the bovine rectum and their functions during growth, in relation to different diets. Fecal samples were collected from 6‐, 12‐, 18‐ and 24‐month cattle fed high‐fat diet, and healthy female parents fed regular diet. Total DNA was amplified (V3–V4 of 16S rRNA) and submitted to barcode‐DNA pyrosequencing. Intestinal microbiota profiles and functions were then analyzed. RESULTS: A total of 114 512 operational taxonomic units were detected from the 1 802 243 sequences obtained. In 6‐month‐old and female parent groups, the top three abundant phyla were Bacteroidetes (37.6%, 32.2%), Firmicutes (34.4%, 48.2%) and Proteobacteria (9.1%, 6.3%); in the 12‐, 18‐ and 24‐month groups, they were Proteobacteria (45.5%, 47.1%, 38.8%), Firmicutes (27.4%, 22.2%, 20.1%) and Bacteroidetes (14.9%, 19.4%, 17.7%), respectively. Paludibacter and Desulfopila in abundance showed negative ( P < 0.001) and positive ( P < 0.05) correlation, respectively, to cattle weight gain through metagenomic functional prediction of methane, cysteine and methionine metabolism. Meanwhile, cofactor/vitamin and amino acid metabolic processes were significantly higher in bacteria from the regular diet group than high‐fat diet groups, with markedly lower cellular processes and signaling, and reduced glycan biosynthesis and metabolism ( P < 0.01). CONCLUSIONS: The 6‐month cattle and female parents shared similar intestinal bacteria; the community structure of fecal microbiota was significantly affected by high‐fat diet in older cattle. © 2017 Society of Chemical Industry